2018
DOI: 10.1021/acs.inorgchem.8b00035
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Dinuclear Oxidovanadium(IV) Complexes with Azo Functionalized Tridentate Ligands and μ-Ethoxido Bridge Leading to an Unsymmetric Twisted Arrangement: Synthesis, X-ray Structure, Magnetic Properties, and Cytotoxicity

Abstract: The synthesis of ethoxido-bridged dinuclear oxidovanadium(IV) complexes of the general formula (HNEt)[(VOL)(μ-OEt)] (1-3) with the azo dyes 2-(2'-carboxy-5'-X-phenylazo)-4-methylphenol (HL, X = H; HL, X = NO) and 2-(2'-carboxy-5'-Br-phenylazo)-2-naphthol (HL) as ligands is reported. The ligands differ in the substituents at the phenyl ring to probe their influence on the redox behavior, biological activity, and magnetochemistry of the complexes, for which the results are presented and discussed. All synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 154 publications
1
31
0
Order By: Relevance
“…In continuation of our previous work on the synthesis, characterization, and biological studies of vanadium(V/IV) complexes [8,13,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45], here we report a new mononuclear dioxidovanadium(V) (1) as well as an oxido-bridged dinuclear oxidovanadium(V) (2) complex, each with a tridentate ONO donor Schiff base ligand derived from 2,4-dihydroxybenzaldehyde and 2-amino-4-nitrophenol. Considering the therapeutic potential of the synthesized polyphenolic ligand molecule [27,30,46], corresponding oxidovanadium(V) complexes were synthesized to further investigate their pharmacological activities such as DNA interaction and anticancer activities.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…In continuation of our previous work on the synthesis, characterization, and biological studies of vanadium(V/IV) complexes [8,13,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45], here we report a new mononuclear dioxidovanadium(V) (1) as well as an oxido-bridged dinuclear oxidovanadium(V) (2) complex, each with a tridentate ONO donor Schiff base ligand derived from 2,4-dihydroxybenzaldehyde and 2-amino-4-nitrophenol. Considering the therapeutic potential of the synthesized polyphenolic ligand molecule [27,30,46], corresponding oxidovanadium(V) complexes were synthesized to further investigate their pharmacological activities such as DNA interaction and anticancer activities.…”
Section: Introductionmentioning
confidence: 60%
“…The 1 H NMR spectra of H 2 L show singlet resonances in the downfield region in the range δ = 10.92-8.95, and 8.21 ppm due to -OH, and -CH (azomethine) protons, respectively [42]. The aromatic protons were observed in the expected range between δ = 8.20-6.27 ppm [37]. However, in 1, the spectra suggests a mononuclear vanadium(V) complex and it exhibits a singlet for each -OH and -HC=N in the region 10.34 and 9.39, ppm respectively [42].…”
Section: Nmr Spectramentioning
confidence: 96%
“…It can be seen from the table data that both complexes can effectively against the HeLa cells. The effect of complex 2 is better than that of cisplatin and some other complexes …”
Section: Resultsmentioning
confidence: 99%
“…12,13 Many new vanadium-based complexes thus have been constantly explored as potential chemotherapeutic agents for cancer treatments since Krahl et al reported the antitumor activity of the first vanadium derivative vanadocene dichloride against Ehrlich cancer in 1983 (Figure 1). 14−23 For example, Dinda et al 15 have recently synthesized an ethoxido-bridged dinuclear oxidovanadium(IV) complex with 2-arylazophenol ligands as potential anticancer agents against HeLa cells. Very recently, new mononuclear oxidovanadium-(IV) complexes were developed by Lord et al 16 and Chakrabarti et al, 17 which are cytotoxic toward different cancerous cell lines yet have lower potency against normal cell types.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The use of V-based compounds offers many benefits such as easy synthesis, relatively low cost and low toxicity, high bioavailability, and high selectivity toward cancer cells. , Furthermore, vanadium can readily expand its coordination sphere and easily switch between different oxidation states V­(III), V­(IV), and V­(V) in biological systems, which probably plays important roles in the biological effects of vanadium compounds as potential therapeutic agents. , Many new vanadium-based complexes thus have been constantly explored as potential chemotherapeutic agents for cancer treatments since Krahl et al reported the antitumor activity of the first vanadium derivative vanadocene dichloride against Ehrlich cancer in 1983 (Figure ). For example, Dinda et al have recently synthesized an ethoxido-bridged dinuclear oxidovanadium­(IV) complex with 2-arylazophenol ligands as potential anticancer agents against HeLa cells. Very recently, new mononuclear oxidovanadium­(IV) complexes were developed by Lord et al and Chakrabarti et al, which are cytotoxic toward different cancerous cell lines yet have lower potency against normal cell types.…”
Section: Introductionmentioning
confidence: 99%